Knowledge on safe sex practices among undergraduate university students at Chuka University, Kenya - Kiraki, Monicah W.; Murumia, Julius G.; Muchiri, Francis G. (International Journal Of Community Medicine And Public Health, 2023)
Background: The youth and adolescents constitute a quarter of the sexually active population and they represent almost half of all new STI cases globally. However, there is limited current data on knowledge of safe sex practices among Kenyan university students. This study sought to assess knowledge on safe sex practices among undergraduate students. Methods: A cross-sectional analytical study design was adopted for this study. A self-administered questionnaire was used to obtain data from undergraduate students. Simple random sampling method was used to sample the participants. Data were analysed using the statistical package of social sciences (SPSS) v.24. Results: The mean age of the participants was 21.37 (±1.75) years. There were more males (56.5%) than females. Majority of participants (63.1%) came from rural areas and more than three-quarters were Christians (88.6%). Majority were single (83.8%) and most were residing in private hostels (71.9%). The mean knowledge score was 68.15 (±21.59)%. Significant predictors of knowledge level were the place of birth and place of residence; p=0.027, AOR=1.975 and p=0.026, AOR=0.477 respectively. Conclusions: The findings indicated that the University students had high knowledge of safe sex practices which was associated with their place of birth and residence. There is a need to assess if the high knowledge translates to practice among the students. The institutions of higher learning should continue to teach age-appropriate safe sexual practices to the students such as sexually transmitted infections, contraception and other related topics.